Pengaruh Model Pembelajaran Project Based Learning (PjBL) dalam Meningkatkan Keaktifan Belajar Siswa pada Mata Pelajaran Sejarah Kebudayaan Islam (SKI) - Siti Marwah Nurmuffidah; Asep Dudi Suhardini; Dinar Nur Inten (Bandung Conference Series: Islamic Education, 2024)
Abstract. The learning process at SDIT Al-Maqom experiences difficulties in student learning activeness in history of islamic culture which still uses traditional or conventional methods. This research aims to determine the condition of active learning of class IV students at SDIT Al-Maqom before and after the implementation of the Project Based Learning (PjBL) learning model and the influence on this learning model. This type of research is quantitative with a quasi-experimental approach model. The results of this research show that 1) The condition of students' activeness before the Project Based Learning (PjBL) learning model was implemented has decreased, as can be seen from the observation sheet which is categorized as "less active and the test on the pretest is at an average which is in the "sufficient" category. 2) The condition of activeness learning after it was implemented improved as shown in the posttest average in the "very good" category with the results of the observation sheet in the "active" category. 3) The influence of the Project Based Learning (PjBL) learning model can increase student learning activity. This can be seen from the results of the Paired-Samples t-Test which obtained a Sig value, so it can be concluded that Ho is rejected and Ha is accepted, there is a significant influence on the use of the Project Based Learning (PjBL) learning model. Thus, it can be concluded that there is a significant influence on the Project Based Learning (PjBL) learning model in increasing the learning activity of class IV students in the History of Islamic Culture (SKI) at SDIT Al-Maqom. Abstrak. Proses pembelajaran di SDIT Al-Maqom mengalami kesulitan dalam keaktifan belajar siswa dalam mata pelajaran Sejarah Kebudayaan Islam (SKI) yang masih menggunakan metode tradisional atau konvesional. Penelitian ini bertujuan untuk mengetahui kondisi keaktifan belajar siswa kelas IV SDIT Al-Maqom sebelum dan sesudah diterapkan model pembelajaran Project Based Learning (PjBL) serta pengaruh pada model pembelajaran tersebut. Jenis penelitian ini adalah kuantitatif dengan model pendekatan quasi eksperimen. Hasil penelitian ini menujukan 1) Kondisi keaktifan siswa sebelum diterapkan model pembelajaran Project Based Learning (PjBL) menurun dapat dilihat dari lembar observasi yang berkategori “kurang aktif” dan tes pada pretest pada rata-rata yang berkategori ”cukup”. 2) Kondisi keaktifan belajar setelah diterapkan menjadi meningkat ditunjukan dalam perolehan rata-rata posttest dengan kategori “baik sekali” dengan hasil lembar observasi berkategori “aktif”. 3) Pengaruh model pembeljaran Project Based Learning (PjBL) dapat meningkatkan keaktifan belajar siswa. Hal ini dapat dilihat dari hasil uji Paired-Samples t-Tes yang memperoleh nilai Sig. 2 tailed, maka dapat disimpulkan bahwa Ho ditolak dan Ha diterima terdapat pengaruh yang signifikan pada penggunaan model pembelajaran Project Based Learning (PjBL). Dengan demikian, dapat disimpulkan terdapat pengaruh yang signifikan pada model pembelajaran Project Based Learning (PjBL) dalam meningkatkan keaktifan belajar siswa kelas IV pada mata pelajaran Sejarah Kebudayan Islam (SKI) di SDIT Al-Maqom.